Perbandingan Usability Tiket.com dan Travelokadengan Metode SUS - Aji Kintan Amara; Syahiid Ilmi; Yustian Servanda; Pramudya Prima Insan (Nolsatu Publisher, 2026)
This study aims to analyze and compare the level of usability between two prominent digital travel booking platforms in Indonesia, namely Tiket.com and Traveloka. The background of this research lies in the criticality of superior user experience in determining competitive advantage within the fierce digital service landscape. The main objective is to quantitatively measure and analyze the difference in usability scores between the two platforms. The methodology utilizes a quantitative approach by implementing the standard System Usability Scale (SUS) questionnaire. The questionnaire consists of 10 alternating positive and negative items, presented using a 5-point Likert scale. These items are repeated for each application to obtain individual usability scores. The survey will be distributed to 30 respondents active users. The results are expected to specifically identify the relative strengths and weaknesses of both applications, providing strategic input for system developers to enhance user interface quality and achieve optimal customer satisfaction.